Cuidados paliativos en el control de la hipertensión arterial del adulto y adulto mayor. Yaruquíes, 2017 - Carla Noemí, Garzón Vera (2017)
A descriptive-transversal study with a mix focus was conducted to propose nursing actions directed at the palliative care of the adult and hypertensive elderly patients, from a family, community and intercultural approach. The population was made up of the total number of patients (92), with a diagnosis of CNCD treated at the Yaruquíes Health Sub-Center in Riobamba, between April and June 2017, who agreed to participate in the research, With ages equal or superior to 20 years and optimal state of mental health, who resided permanently in that area of influence during the study period and who are in their domicile at the moment in which the instruments will be applied. It was observed a predominance of the age group of more than 65 years, feminine gender, practice of the catholic religion, mestizo ethnic self-identification, married civil status, level of basic schooling, housewives occupation and farmers; As well as the family history of hypertension. Most patients surveyed consider that the dimensions of quality of life and patient satisfaction with health services are in the average range established in the rating scale; As a result, that could be related to the damages that this disease causes on the individual, the family and the community. The nursing care plan was designed from a palliative approach of family, community and intercultural scope, based on Dorothea Orem's theory of self-care.